Transcriptome analysis of Bombyx mori larval midgut during persistent and pathogenic cytoplasmic polyhedrosis virus infection. - Anna Kolliopoulou; Filip Van Nieuwerburgh; Dimitrios J Stravopodis; Dieter Deforce; Luc Swevers; Guy Smagghe (PLoS ONE)
Many insects can be persistently infected with viruses but do not show any obvious adverse effects with respect to physiology, development or reproduction. Here, Bombyx mori strain Daizo, persistently infected with cytoplasmic polyhedrosis virus (BmCPV), was used to study the host's transcriptional response after pathogenic infection with the same virus in midgut tissue of larvae persistently and pathogenically infected as 2nd and 4th instars. Next generation sequencing revealed that from 13,769 expressed genes, 167 were upregulated and 141 downregulated in both larval instars following pathogenic infection. Several genes that could possibly be involved in B. mori immune response against BmCPV or that may be induced by the virus in order to increase infectivity were identified, whereas classification of differentially expressed transcripts (confirmed by qRT-PCR) resulted in gene categories related to physical barriers, immune responses, proteolytic/metabolic enzymes, heat-shock proteins, hormonal signaling and uncharacterized proteins. Comparison of our data with the available literature (pathogenic infection of persistently vs. non-persistently infected larvae) unveiled various similarities of response in both cases, which suggests that pre-existing persistent infection does not affect in a major way the transcriptome response against pathogenic infection. To investigate the possible host's RNAi response against BmCPV challenge, the differential expression of RNAi-related genes and the accumulation of viral small RNAs (vsRNAs) were studied. During pathogenic infection, siRNA-like traces like the 2-fold up-regulation of the core RNAi genes Ago-2 and Dcr-2 as well as a peak of 20 nt small RNAs were observed. Interestingly, vsRNAs of the same size were detected at lower rates in persistently infected larvae. Collectively, our data provide an initial assessment of the relative significance of persistent infection of silkworm larvae on the host response following pathogenic infection with CPV, while they also highlight the relative importance of RNAi as an antiviral mechanism.